Comparative effects of inorganic and three forms of organic trace minerals on growth performance, carcass traits, immunity, and profitability of broilers - Khatun, Anguara; Chowdhury, Sachchidananda Das; Roy, Bibek Chandra; Dey, Bapon; Haque, Azimul; Chandran, Bakthavachalam (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The experiment was conducted to investigate the comparative effects of inorganic trace minerals (ITM) and three forms of organic trace minerals (OTM) (propionate, metho-chelated, and proteinate) on growth performance, edible meat yield, immunity, and profitability of commercial broilers. Materials and methods: A corn-soya based mash diet comprising four treatments each of 10 replicates were fed to 720 day-old Cobb 500 broiler chicks for 35 days (starter diet 0–21 days and grower diet 22–35 days). The diets for comparison were as follows: diet 1: control diet with ITM premix at 1 kg/ton of feed (T1); diet 2: control diet supplemented with propionate trace minerals at 600 gm/ton (T2); diet 3: control diet supplemented with metho-chelated trace minerals at 500 gm/ton by reducing 225 gm methionine/ton of feed (T3); and diet 4: control diet supplemented with proteinate trace minerals at 500 gm/ton of feed (T4). Growth performance, carcass yield, and antibody titer (AT) data were recorded. Data were analyzed and interpreted using SAS Computer Package Program version 9.1. Results: Feeding propionate and proteinate OTM showed similar performance. Birds fed these two types (propionate and proteinate) or OTM had better performance in comparison with those receiving ITM and metho-chelated one. Proteinate group produced more wing meat and propionate group showed higher breast and drumstick meat yield as compared with those received the metho-chelated trace mineral and ITM. The birds belonging to OTM groups showed significantly higher AT level against infectious bursal disease. Proteinate minerals groups showed higher profitability followed by propionate fed broilers. Conclusion: Two forms of OTM, propionate and proteinate improved performance of commercial broilers over those of ITM and metho-chelated one. J. Adv. Vet. Anim. Res., 6(1): 66-73, March 2019